E-PTJOB: Application Link And Match Job Seekers Based On Android - Alfredo Pasaribu; Yoas Arnest Soetopo; Dedy Prasetya Kristiadi; S Sutrisno (IJISTECH (International Journal of Information System and Technology), 2022)
The impact of the corona virus disease-19 has caused many companies to close and workers to be laid off. This also has an impact on the decline in economic growth and the level of welfare of the population in the affected areas. The need for labor management is an urgent and serious matter. The creation of the e-PTJOB application is a breakthrough to deal with this problem. This part-time job seeker application is made with a link and match model where job seekers are met with job seekers based on the needs or requests of job seekers who are not limited by education level. Jobs given by job seekers are temporary with payment based on duration of time, meanwhile prospective workers can choose work categories based on location, level of education and work to be done. The e-PTJOB application begins with registration of job seekers and job seekers where each actor provides data according to his capacity. Furthermore, job seekers will make a deposit on the application via transfer of a nominal amount that will be used to pay workers according to job criteria and work duration. Workers who have already done work will get paid according to the job offer. This e-PTJOB application will assist the government in dealing with cases of unemployment of productive age which are not limited by education level as well as increase the income level of the population in the region